2023
DOI: 10.3390/microorganisms11040863
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Plant Growth-Promoting Rhizobacteria for Sustainable Production of Bermudagrass Forage

Abstract: A two-year study was conducted in bermudagrass hay fields in central Alabama to estimate the potential of plant growth-promoting rhizobacteria (PGPR) as a tool for sustainable agriculture in forage management. This study compared the effects of two treatments of PGPR, applied with and without lowered rates of nitrogen, to a full rate of nitrogen fertilizer in a hay production system. The PGPR treatments included a single-strain treatment of Paenibacillus riograndensis (DH44), and a blend including two Bacillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Hence, the increased grain yield (38-39%), along with no changes in the total chlorophyll content even under the 70% reduced doses of nitrogen fertilizer, can be attributed to the cumulative effects of the plant-growth-promoting traits possessed by each of the crew members of all four consortia in this study. Several other studies reported similar findings, namely that plant-growth-promoting traits of endophytic bacteria augmented the nutrient uptake and enhanced rice yields [68][69][70] and yields of zucchini [71] and bermudagrass [72]. The endophytic strain of Lysinibacillus sphaericus [56] also demonstrated various aspects of plant-growth-promoting traits, such as those of the four consortia reported in the present study, which could accelerate plant growth along with fortifying the plant structure to provide resistance to phytopathogens.…”
Section: Discussionsupporting
confidence: 86%
“…Hence, the increased grain yield (38-39%), along with no changes in the total chlorophyll content even under the 70% reduced doses of nitrogen fertilizer, can be attributed to the cumulative effects of the plant-growth-promoting traits possessed by each of the crew members of all four consortia in this study. Several other studies reported similar findings, namely that plant-growth-promoting traits of endophytic bacteria augmented the nutrient uptake and enhanced rice yields [68][69][70] and yields of zucchini [71] and bermudagrass [72]. The endophytic strain of Lysinibacillus sphaericus [56] also demonstrated various aspects of plant-growth-promoting traits, such as those of the four consortia reported in the present study, which could accelerate plant growth along with fortifying the plant structure to provide resistance to phytopathogens.…”
Section: Discussionsupporting
confidence: 86%